2012
DOI: 10.1002/cncr.27788
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Dickkopf‐related protein 1 is related to lymphatic metastasis and indicates poor prognosis in intrahepatic cholangiocarcinoma patients after surgery

Abstract: BACKGROUND: Dickkopf-related protein 1 (DKK1) has been reported involved in metastasis and invasion in several tumors. This study sought to investigate the prognostic value of DKK1 in intrahepatic cholangiocarcinoma (ICC) and its role in promoting ICC metastasis. METHODS: Tissue microarrays of 138 ICC patient samples were employed to detect DKK1, vascular endothelial growth factor C (VEGF-C), and matrix metalloproteinase 9 (MMP9) expression using immunohistochemistry. The prognostic significances were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 73 publications
3
67
1
Order By: Relevance
“…Numerous studies have shown that DKK1 was implicated in the control of various pathological and physiological processes, including adult hippocampal neurogenesis [5], osteoclastogenesis [6], tumor cell proliferation, survival, migration and invasion [7,8]. However, the role of DKK1 in tumor biology is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that DKK1 was implicated in the control of various pathological and physiological processes, including adult hippocampal neurogenesis [5], osteoclastogenesis [6], tumor cell proliferation, survival, migration and invasion [7,8]. However, the role of DKK1 in tumor biology is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of DKK1 has also been reported in breast and kidney cancers [13]. A recent research article showed that high expression of DKK1 is related to lymphatic metastasis and indicates poor prognosis in intrahepatic cholangiocarcinoma (ICC) patients after surgery, vice versa, depletion of DKK1 using small interfering RNA results in a decrease in ICC cell migration and invasion [8]. Taken together, all these findings suggest that DKK1 performs an oncogenic or a tumor-suppressing function depends on the cell type or context.…”
Section: Introductionmentioning
confidence: 99%
“…CCA usually metastasize and cause relapse because it is commonly diagnosed in the advanced stage of the disease, and leads to poor prognosis [2][3][4]. Many studies have revealed that numerous genes are involved in CCA [5][6][7][8][9] and many therapeutic strategies have been developed to treat CCA [10][11][12]; however, the survival rate for CCA patients is still low [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other candidate serum markers that have been reported for the diagnosis of CCA include sperm-specific protein 411 [58], dickkopf-related protein 1 [59], and KL-6 mucin [60]. Nevertheless, larger validation studies are needed to confirm these findings and establish the potential markers clinically.…”
Section: Resultsmentioning
confidence: 99%